The determinatiants of labour productivity growth in Malaysia / Nur Farihah Mohammad Azhar - Mohammad Azhar, Nur Farihah (2022)
Productivity measures an organization's or country's capacity to create more money or value added. Malaysia is expected to shift to a high-income economy between 2024 and 2028, reflecting the country's economic development trajectory during the previous decades. As Malaysia strives to become a developed country with a high standard of living, great productivity in manufacturing processes is critical. The aim of this research is to find out what factors have an impact on Malaysia's labour productivity as well as to investigate how independent variables influence the dependent variable. The research was performed using secondary data from economic indicators, which are real wages, inflation, foreign direct investment (FDI), unemployment, and employment rate. The research sample consisted of time-series data on Malaysia's labour productivity from 1990 until 2020. According to the results, there are three significant factors in this research, which are real wages, foreign direct investment, and the inflation rate, while the unemployment and employment rates are not significant. The result of this research showed that the independent variables, which are real wages, foreign direct investment, and employment rate, showed a positive correlation. Meanwhile, the inflation rate and unemployment rate show a negative correlation with labour productivity. Keywords: inflation, foreign direct investment (FDI), unemployment, real wages and employment rate, labour productivity